The knowledge gap between intended and attained curriculum in Ethiopian teacher education: identifying challenges for future development. Issue 1 (2nd January 2021) - Alemu, Mekbib; Kind, Vanessa; Basheh, Mesfin; Michael, Kassa; Atnafu, Mulugeta; Kind, Per; Rajab, Taha
ABSTRACT: This investigation of physics teacher education in Ethiopia reveals a significant gap between the physics knowledge of pre-service teachers (PSTs) attained during training and that of the intended curriculum setting out expectations for their knowledge. Data were obtained by a test probing PSTs' physics knowledge (attained curriculum); analysis of teacher education curriculum documents (intended); and video-recording, observation and analysis of lectures delivered to pre-service teachers at four Colleges of Teacher Education (implemented). These illustrate that implementation focuses on high-level, abstract knowledge delivered mainly via mathematical approaches, offering limited opportunities for learning basic concepts by debate. An outcome of current practice is that physics teachers lack the necessary subject knowledge to teach effectively, leading successive generations of Ethiopian students to under-achieve. The paper argues for change to enable Ethiopia to achieve its aim of raising educational achievement and societal productivity to become a low-middle income nation by 2025.